Detecting illegal cyanide fishing: Establishing the evidence base for a reliable, post-collection test. (January 2020) - Murray, Joanna M.; Bersuder, Philippe; Davis, Scott; Losada, Sara
Abstract: Ornamental fish have been legally harvested since the 1930's but in the 60's, cyanide fishing was first documented. Target fish exposed to the chemical are temporarily paralysed making them easier to catch, but with high post-capture mortality and significant ecological impacts, its use is banned in most exporting countries. To differentiate illegally caught fish from those sustainably collected, efforts to develop a post-collection detection test began nearly 30 years ago. However, even the most promising approach has been questioned by other researchers as unrepeatable under different experimental conditions. In this paper we summarise the evidence-base for establishing a cyanide detection test for live fish by evaluating current approaches. We describe the key knowledge gaps which continue to limit our progress in implementing a screening programme and highlight some alternative solutions which may provide greater short to medium term opportunities to prevent the illegal practise before fish enter the supply chain. Highlights: Cyanide fishing is used by some fishers to collect live fish for trade. Cyanide is toxic to fish and leads to high mortality along the supply chain. Thiocyanate, a by-product of cyanide metabolism is the target compound for a test. Non-invasive detection of thiocyanate was reported but is since unrepeatable. Toxicokinetic studies, test development and management interventions are needed.